Biomimetic virus-like mesoporous silica nanoparticles improved cellular internalization for co-delivery of antigen and agonist to enhance Tumor immunotherapy. (31st December 2023) - Gao, Yuan; Zhang, Yingxi; Xia, Hong; Ren, Yuqing; Zhang, Haibin; Huang, Siwen; Li, Meiju; Wang, Yongjun; Li, Heran; Liu, Hongzhuo
Abstract: Nanocarrier antigen-drug delivery system interacts specifically with immune cells and provides intelligent delivery modes to improve antigen delivery efficiency and facilitate immune progression. However, these nanoparticles often have weak adhesion to cells, followed by insufficient cell absorption, leading to a failed immune response. Inspired by the structure and function of viruses, virus-like mesoporous silica nanoparticles (VMSNs) were prepared by simulating the surface structure, centripetal-radialized spike structure and rough surface topology of the virus and co-acted with the toll-like receptor 7/8 agonist imiquimod (IMQ) and antigens oocyte albumin (OVA). Compared to the conventional spherical mesoporous silica nanoparticles (MSNs), VMSNs which was proven to be biocompatible in both cellular and in vivo level, had higher cell invasion ability and unique endocytosis pathway that was released from lysosomes and promoted antigen cross-expression. Furthermore, VMSNs effectively inhibited B16-OVA tumor growth by activating DCs maturation and increasing the proportion of CD8 + T cells. This work demonstrated that virus-like mesoporous silica nanoparticles co-supply OVA and IMQ, could induce potent tumor immune responses and inhibit tumor growth as a consequence of the surface spike structure induces a robust cellular immune response, and undoubtedly provided a good basis for further optimizing the nanovaccine delivery system.